Preparing Protocols for Institutional Review Boards - Charles M. Lyons (Journal of Research in Rural Education, 1983)
Federal statute and regulations deal extensively with the conduct of research involving human subjects. The Institutional Review Board mechanism was established to comply with these regulations which require peer review and approval of research involving the use of human subjects and funded by the U.S. Department of Health and Human Services. Because of the gravity of the ethical issue involved in such research, the review mechanism has commonly been extended by schools, agencies, universities, and hospitals to include review and approval of all proposals for research, regardless of extent of funding or source of funding. This manuscript is directed at all researchers who utilize human subjects and who therefore are very likely to be in positions which will require them to develop material for presentation to Institutional Review Boards. In it, the composition and process of the IRB are discussed. The basic elements of informed consent and the criteria against which proposals are judged are presented. Finally, a sample protocol format is presented.